An ABCB11 variant registry and novel knockin mouse model of PFIC2 based on the clinically relevant ABCB11 E297G variant - Eric L. Bell; Jennifer K. Truong; Youhwa Jo; Adrianne Kolpak; Lauren Chunn; Natalie Syverud; Melida Mahinic; Jessica R. Durrant; Eitan Hoch; Bharat Reddy; Patrick Stoiber; John P. Miller; et al. (Journal of Lipid Research, 2025)
Progressive familial intrahepatic cholestasis type 2 (PFIC2) is a rare pediatric cholestatic liver disease caused by genetic deficiency in the bile salt export pump (BSEP, ABCB11). BSEP is an ATP-binding cassette transporter and the primary regulator of hepatic bile acid efflux. Loss of BSEP function in PFIC2 leads to cholestasis and intrahepatic accumulation of bile acids, the native toxicity of which drives progressive liver injury, in a manner that correlates with ABCB11 genotype. Here, to support ongoing PFIC2 research, we present two novel translational tools, 1) a codified evidence-based catalog of published disease relevant ABCB11 mutations and 2) a knockin mouse model of the PFIC2-associated missense variant E297G. Using a combination of AI-based indexing of the literature and manual review, we identified 476 nonbenign ABCB11 variants in published patients with cholestatic disease, of which 240 were associated with PFIC2. Additionally, we present phenotypic validation of a novel knockin mouse model of the cholestasis-associated ABCB11 E297G variant. BsepE297G homozygous mice recapitulate the core molecular and pathophysiological aspects of PFIC2, including perturbed Bsep processing and membrane trafficking, cholestasis, and hepatotoxicity. Moreover, and consistent with clinical data, pharmacological ileal bile acid transporter inhibition improved the cholestatic phenotype of BsepE297G mice through increased fecal bile acid excretion. Together, these tools can support clinical and translational efforts to advance understanding and treatment of PFIC2.